Perlindungan Hak Asasi Manusia dalam Hukum Tata Negara Indonesia - Lia Mastaria Duda; Roslan Ishak; Roy Marthen Moonti (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2025)
The protection of human rights is a fundamental element of Indonesian constitutional law. Although it has been constitutionally regulated through the 1945 Constitution and a number of laws, the implementation of human rights protection still faces various challenges, including discrimination, violence by the authorities, and inconsistency in legal politics. This study aims to analyze the effectiveness of the constitutional law system in ensuring human rights protection as well as the role of state institutions such as Komnas HAM, the legislature, the executive, and the judiciary. The results show that human rights protection has not been optimal due to weak coordination, lack of accountability, and lack of support for independent institutions. The conclusion emphasizes the importance of legal reform, institutional strengthening, and harmonization between national law and international human rights standards. Suggestions include improving human rights education, empowering civil society, and consistent law enforcement to create a democratic and just rule of law.